Morphotropic Phase Boundary in the Pb‐Free (1 − x)BiTi3/8Fe2/8Mg3/8O3–xCaTiO3 System: Tetragonal Polarization and Enhanced Electromechanical Properties. (26th March 2015) - Mandal, Pranab; Manjón‐Sanz, Alicia; Corkett, Alex J.; Comyn, Tim P.; Dawson, Karl; Stevenson, Timothy; Bennett, James; Henrichs, Leonard F.; Bell, Andrew J.; Nishibori, Eiji; Takata, Masaki; Zanella, Marco; et al.
<x xml:space="preserve">Abstract</x> Lead‐free bismuth‐based perovskite oxides with polarization directed along the [001]p primitive perovskite unit cell edge, analogous to tetragonal PbTiO3, are synthesized at ambient pressure. Enhanced piezoelectric properties, large polarizations, and high depolarization temperatures are observed in the wide morphotropic phase boundary region formed with a rhombohedral phase, with up to 92.5% Bi on the perovskite A site.